Ask a question
0 0


How do you solve this problem

Tutors, please sign in to answer this question.

1 Answer

Let's start by getting all the variable terms on the left side of the equation and constant terms on the right. To do that, we always apply the opposite operation to the term we're interested in; additionally, to maintain the equality, what we do to one side we always do to the other. Let's get the -8y term to the left side by adding 8y to each side then combine like terms.

-13y + 20 = -8y - 25
+8y          +8y
-5y + 20 = -25

Now, let's subtract 20 from each side.

-5y + 20 = -25
      -20     -20
-5y = -45

What is the operation occurring between the -5 and y? Multiplication. So we do the opposite. Let's divide each side by -5 so that the coefficient of y goes to 1 (we are only interested in what y is equal to, not -5y).

-5y = -45
-5       -5

The -5/-5 = 1, so y = -45/-5 = 9